Analysis of Present Conditions and Prospects of the Labour Market Development in Russia - Volynskyi, Vladymir; Zaitzev, Victor (Comparative Economic Research. Central and Eastern Europe, 2010)
In this article, based on the statistical data analysis, we consider the labour market in the contemporary Russia in face of global economic crises. In our opinion, two kinds of programs should be in Russia interest: coordination of unemployment benefits with vocational training, retraining or additional education; using the compelled holidays for additional education and retraining. The target programs directed on strengthening employees’ positions with a high educational level on the labour market are extremely necessary in the Russian conditions. In order to decide on specific problems special departments should be created in the Ministry of Work and Social Development of the Russian Federation.